Pengaruh Model Project Based Learning Berbantuan MEGASI (Media Gambar Berseri) terhadap Keterampilan Menulis Teks Deskripsi Siswa Kelas V Sekolah Dasar - Deti Indah Kiranti; Neneng Sri Wulan; Nadia Tiara Antik Sari (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2024)
This research was conducted to determine the importance of descriptive text writing skills that students must master to support learning. However, in reality, it turns out that students' descriptive text writing skills are still low. One of the causes of these low skills is that the learning model used by teachers is still a conventional teacher-centered model, so that students are not actively involved in learning. The aim of this research is to determine the influence and improvement through action in two different groups using four indicators of descriptive text writing skills. The experimental group used a Project Based Learning model assisted by MEGASI, and the control group used a cooperative learning model. The research method used was quasi-experimental with a non-equivalent control group design and a sample of 42 people was selected using a purposive sampling technique. The research results showed that the improvement in descriptive text writing skills of students in the experimental class was better than students in the control class. There is a positive influence in the use of the Project Based Learning model assisted by MEGASI is serial image media on the descriptive text writing skills of fifth grade elementary school students.